STRATEGI KOMUNIKASI SHOPEE DALAM MENINGKATKAN PENJUALAN TERHADAP KAUM MILLENIAL MELALUI FITUR PAYLATER - Novyanthi Adityaa; Hasnun Jauhari Ritonga (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The Shopee app is one of the most downloaded online retail apps and is used as a digital storefront to search for goods or personal needs using electronic devices as gadgets . Shopee has launched many features to help consumers meet their needs more easily and quickly, different from buying offline or buying directly at the store. Startups like Shopee with a target market of millennials or people with busy jobs who do not have time to shop in person, this marketing strategy has had a very good impact on the sales curve of many stores. recorded on this single application. Judging from the media network data, Shopee is really the most downloaded application by the public because of the attractive features it brings, which is also one of the company's marketing tactics in the form of an organization. . Online shop. However, in this endeavor, there are also pros and cons regarding the payment feature offered by this app, which gives rise to the opinion of scholars of this payment law from the point of view of and the point of view of Islam, in order to educate people so that they do not use this feature carelessly, they should think about the risks of the world and more.